2018
DOI: 10.1021/acsanm.8b01117
|View full text |Cite
|
Sign up to set email alerts
|

Natural Laterite as a Catalyst Source for the Growth of Carbon Nanotubes and Nanospheres

Abstract: Carbon nanotubes (CNTs), the closest structure to ideal one-dimensional (1D) conductors, have stimulated substantial interest in the last decades for many applications in the field of nanotechnology. Unfortunately, the high cost of efficient metal catalysts limits the large-scale exploitation of carbon nanomaterials' synthesis processed by chemical vapor deposition (CVD). However, minor or even trace amounts of metal or metal oxides in the ideal form to be used as catalysts can be easily found in almost all-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…It has been confirmed that hemicelluloses started decomposition easily, with the weight loss mainly happening at 220~315 • C, and cellulose pyrolysis was focused at a higher temperature range (315~400 • C) [31]. Thus, due to the pyrolysis occurring under nitrogen protection, the dramatic weight loss for EAc NH3 -180 and ACl NH3 -180 was mainly due to the thermal degradation of the hemicelluloses and partial cellulose [32], though it displayed a thermal curve with a single weight loss dip when a one-step oxidative degradation process of crystalline carbon with oxygen occurred [33]. When the HTC temperature was higher than 230 • C, almost all the holocelluloses were converted into amorphous carbon, with a very high solid residue reaching 65% and 60% for the EAc NH3 -280 and ACl NH3 -280 samples.…”
Section: Tgamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that hemicelluloses started decomposition easily, with the weight loss mainly happening at 220~315 • C, and cellulose pyrolysis was focused at a higher temperature range (315~400 • C) [31]. Thus, due to the pyrolysis occurring under nitrogen protection, the dramatic weight loss for EAc NH3 -180 and ACl NH3 -180 was mainly due to the thermal degradation of the hemicelluloses and partial cellulose [32], though it displayed a thermal curve with a single weight loss dip when a one-step oxidative degradation process of crystalline carbon with oxygen occurred [33]. When the HTC temperature was higher than 230 • C, almost all the holocelluloses were converted into amorphous carbon, with a very high solid residue reaching 65% and 60% for the EAc NH3 -280 and ACl NH3 -280 samples.…”
Section: Tgamentioning
confidence: 99%
“…due to the thermal degradation of the hemicelluloses and partial cellulose [32], though it displayed a thermal curve with a single weight loss dip when a one-step oxidative degradation process of crystalline carbon with oxygen occurred [33]. When the HTC temperature was higher than 230 °C, almost all the holocelluloses were converted into amorphous carbon, with a very high solid residue reaching 65% and 60% for the EAcNH3-280 and AClNH3-280 samples.…”
Section: Tgamentioning
confidence: 99%
“…Laterite is both a soil and rock type rich in Fe and Al contents and is considered to be formed via intensive and prolonged weathering of the underlying parent rock. Kumar and colleagues employed Ni laterite powder from Tiebaghi in New Caledonia for CNTs and CNSs syntheses via CVD using ethylene as a carbon source [68]. In the used laterite, the major micro-contents found were goethite, FeO(OH), and hematite (Fe 2 O 3 ) along with a minor amount of phyllosilicates.…”
Section: Natural Lateritementioning
confidence: 99%
“…Ni and Fe are known catalysts for CVD growth of carbon nanotubes or other carbon nanostructures [17], and it is possible to observe a few such filamentous structures (Figure 7c, in orange). However, the formation of catalysts chunks, which cannot catalyze CNTs growth, may lead to further coating by amorphous carbon [18] (Figure 7c, in yellow). Then, the amorphous carbon grows preferably in clusters, increasing in size until carbon spheres are formed.…”
Section: Effect Of the Temperature During Cvdmentioning
confidence: 99%